Tradisi Pesantren dan Kosmopolitanisme Islam di Masyarakat Pesisir Utara Jawa - Syamsul Hadi (Laboratorium Sosiologi Universitas Nahdlatul Ulama Indonesia Jakarta, 2021)
This study aims to explain the cosmopolitan of Islam and the existence of pesantren that related to the preservation of Islamic traditions in coastal communities. The implementation of Islamic values and teachings that are tolerant of local culture and wisdom, of course, is the main concern of pesantren in building social cohesiveness. This social research uses qualitative methods with constructivism paradigm. Data mining was carried out through in-depth interviews plus document reviews or literature studies related to the object of research. The results showed that the pesantren tradition had deep roots in the northern coastal community of Java, such as the Pangwiwahan, Muludan, Manaqiban ceremonies and the rituals of reading Tahlilan /Yasinan and Shalawatan which dominated the traditional ceremonies like Slametan or Kenduren (local traditions). This tradition seems to be influenced by the characteristics of cosmopolitan Islam which has long developed in coastal communities of Java, especially in the bandar environment. The cosmopolitanism culture is characterized by a fluid atmosphere of communication, openness to outsiders and hospitality. So, in the development of this cosmopolitanism character, it also forms a pluralistic social formation in urban settlements, where each other respects and holds the same values, namely tepo selira. The formation of the pattern and character of the community is not spared because of the influence of the bandar’s culture. That bandar and ports are not merely places of exchange or entry and exit of goods and people. In fact, there is also cultural contact, the exchange of ideas and the intersection of the lifestyles of actors from various nations with different backgrounds. Because the ability to adapt to all differences and be selective about the chosen novelty, it is proven that the pesantren develops dynamically, but still has a strong influence among the supporting community.